Development of piezoelectric diaphragm pump - Li, Tao (2013)
In the present work, a piezoelectric diaphragm pump was designed and investigated. The pump uses a piezoelectric diaphragm transducer as the driving component, and two check valves located at the inlet and outlet to control the flow direction. The displacement of the transducer was first measured statically and dynamically. Then the vibration of check valves and the effects of chamber depth were investigated. Finally the pump performance was characterized. Maximum flow rate of 200 mL/min and pressure head of 5 mH2O can be achieved.